Konstruksi Sosial, Budaya dan Ekonomi pada Pola Makan Masyarakat Kelurahan Benteng Somba Opu Kabupaten Gowa - Try Aziz Zulkarnaen; Mubarak Dahlan; Mr. Ahmadin (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2022)
This study examines the eating patterns and habits of the people in Benteng Somba Opu Village, Gowa Regency. The purpose of this study was to determine the views of the people in the Benteng Somba Opu village regarding halal and good food, eating patterns and habits in the community as well as internal and external factors of eating habits in the community. This study uses qualitative data with descriptive analysis. The results showed that the eating patterns and habits of the people in the Benteng Somba Opu Village, Gowa Regency, were influenced by the way of obtaining food sources, eating habits, the family's economic level, and the surrounding environment. The external factors that influence eating patterns and habits are culture, religion, economic factors, media and advertising, while internal factors that can influence eating patterns and habits are emotional associations, physical condition, food availability and the family tradition itself.